Application of Linear Regression in Predicting Education Level and Income of Residents (Case Study: Desa Padang Cermin) - Nst, Anugrah Always; Sihombing, Marto; Ambarita, Indah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Linear regression methods were used to predict education and income levels in Padang Cermin Desa. Padang Cermin Desa has twelve hamlets and a total of 13,055 residents, with 6,135 men and 6,920 women, and 2545 households. The aim of this study is to raise government and community awareness of the importance of education for welfare and a better life in the future. Using existing data, this study can provide a clear picture of the relationship between education levels and income as well as relevant recommendations to improve the quality of life in Padang Cermin Desa. This research uses a quantitative case study design with secondary data collected through hamlet heads and semi-structured interviews. The linear regression equation Y 36900147.57 + 2516320.971X is based on the MAPE value with a result of 28.25% and an accuracy rate of 71.75%. In the case study of applying linear regression to predict the education level and income of residents, the following are some conclusions: The prediction results show that people with elementary school education are estimated to have an income of 421,897,256.1, while people with secondary school education are estimated to have an income of 311,179,133.4. People who completed a senior high school education are estimated to have the highest income of IDR 457,125,749.7, showing the importance of secondary education. Higher education and vocational education still have the potential to be improved, although the income of the population with education is estimated at IDR 64,579,678.25 for Diploma I/II/III and IDR 79,677,604.08 for Diploma IV/Strata I.